2017
DOI: 10.1098/rstb.2016.0050
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cerebellar transcranial direct current stimulation (tDCS) on learning fine-motor sequences

Abstract: One contribution of 13 to a theme issue 'New frontiers for statistical learning in the cognitive sciences'. The cerebellum has been shown to be important for skill learning, including the learning of motor sequences. We investigated whether cerebellar transcranial direct current stimulation (tDCS) would enhance learning of fine motor sequences. Because the ability to generalize or transfer to novel task variations or circumstances is a crucial goal of real world training, we also examined the effect of tDCS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 73 publications
4
19
0
1
Order By: Relevance
“…cerebellar tDCS led to better knowledge of the sequence when compared to sham. The findings here are in accordance with previous work showing the beneficial effect of anodal cerebellar tDCS on motor sequence learning (Ferrucci et al, 2013;Shimizu et al, 2017) but in contrast to a recent report showing the opposite effect (Ballard et al, 2019). Note that in the latter study, a multi-channel montage was used with a net current of 2mA compared to our protocol with 1mA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…cerebellar tDCS led to better knowledge of the sequence when compared to sham. The findings here are in accordance with previous work showing the beneficial effect of anodal cerebellar tDCS on motor sequence learning (Ferrucci et al, 2013;Shimizu et al, 2017) but in contrast to a recent report showing the opposite effect (Ballard et al, 2019). Note that in the latter study, a multi-channel montage was used with a net current of 2mA compared to our protocol with 1mA.…”
Section: Discussionsupporting
confidence: 93%
“…This effect is however not specific to M1. Other studies showed that anodal stimulation of the cerebellum has a similar effect on sequence learning (Ferrucci et al, 2013;Shimizu et al, 2017), but see (Jongkees et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Indeed we showed that modulatory effects of these connections were significantly smaller in patients and did not differ between conditions, probably due to the degeneration in cerebellum. Recent studies in healthy controls have shown that modulation of cerebellar activity using transcranial direct current stimulation (tDCS) can influence motor learning behavior (Block and Celnik, 2013;Cantarero et al, 2015;Ehsani et al, 2016;Ferrucci et al, 2013;Galea et al, 2011;Herzfeld et al, 2014;Shimizu et al, 2017). Specifically, this effect has been shown to be polarity specific; anodal tDCS to cerebellum is thought to enhance neuronal excitability and was shown to enhance learning whereas the opposite effect was evident in some studies.…”
Section: Network Underlying Motor Learning In Cerebellar Degenerationmentioning
confidence: 99%
“…The empirical work of Shimizu et al [22] extends SL research on several important fronts. First, it focuses on visuomotor SL, thereby probing the link between perception and action.…”
mentioning
confidence: 91%